Sewage sludge use in bioenergy production. A case study of its effects on soil properties under Cynara cardunculus L. cultivation - Lag-Brotons, Alfonso J.; Gómez, Ignacio; Navarro-Pedreño, José (Spanish Journal of Agricultural Research, 2015)
Energy crops cultivation is expected to further increase, which represents an opportunity to establish synergies able to enhance key environmental components (i.e. soil). To reach this benefits crop management is crucial and should be properly assessed. The aim of this work is to provide an insight on the effects of sewage sludge compost (SSC) on soil properties, when this material is applied as basal dressing for the cultivation of a Mediterranean energy crop (Cynara cardunculus L.). A 3-years trial (2008/2011) was conducted in Alicante (Southeastern Spain), testing four SSC application rates (0, 30, 50 and 70 t/ha) on a heavy textured Anthrosol. The addition of SSC enhanced soil fertility, primarily increasing organic carbon (Cox), Kjeldahl nitrogen (Nk), available P (PBurriel), CuDTPA and ZnDTPA levels. Comparatively with the control (0 t/ha), 30, 50 and 70 t/ha treatments induced a rise of 11%, 19% and 25% in Nk (Control=1.11 g/kg) and PBurriel (Control=79 mg/kg), while for Cox (Control=11.8 g/kg) was 14%, 21% and 30%. However, these variables apparently did not significantly decrease throughout the experiment, which suggests that the organic matter added was under a stabilization process, favoured by the poor physical properties of the soil. Other elements (NaNH4Ac, KNH4Ac, MnDTPA) were accumulated within the soil as time passed by, as a result of soil status, Mediterranean environmental conditions and crop management. The use of SSC as organic fertilizer represents an effective option to optimize cynara cultivation systems while improving soil quality through enhanced long-lasting organic matter pools.